Facilitating the interpretation of English language proficiency scores: Combining scale anchoring and test score mapping methodologies. (April 2017) - Powers, Donald; Schedl, Mary; Papageorgiou, Spiros
The aim of this study was to develop, for the benefit of both test takers and test score users, enhanced TOEFL ITP ® test score reports that go beyond the simple numerical scores that are currently reported. To do so, we applied traditional scale anchoring (proficiency scaling) to item difficulty data in order to develop performance descriptors for multiple levels of each of the three sections of the TOEFL ITP . A (novel) constraint was that these levels should correspond to those established in an earlier study that mapped (i.e., aligned) TOEFL ITP scores to a widely accepted framework for describing language proficiency – the Common European Framework of Reference (CEFR). The data used in the present study came from administrations of five current operational forms of the recently revised TOEFL ITP test. The outcome of the effort is a set of performance descriptors for each of several levels of TOEFL ITP scores for each of the three sections of the test. The contribution, we believe, constitutes (1) an enhancement of the interpretation of scores for one widely used assessment of English language proficiency and (2) a modest contribution to the literature on developing proficiency descriptors – an approach that combines elements of both scale anchoring and test score mapping.